Targeting the MYC Ubiquitination-Proteasome Degradation Pathway for Cancer Therapy - Sun, Xiao-Xin; Li, Yanping; Sears, Rosalie C.; Dai, Mu-Shui (Frontiers in Oncology, 2021)
Deregulated MYC overexpression and activation contributes to tumor growth and progression. Given the short half-life and unstable nature of the MYC protein, it is not surprising that the oncoprotein is highly regulated via diverse posttranslational mechanisms. Among them, ubiquitination dynamically controls the levels and activity of MYC during normal cell growth and homeostasis, whereas the disturbance of the ubiquitination/deubiquitination balance enables unwanted MYC stabilization and activation. In addition, MYC is also regulated by SUMOylation which crosstalks with the ubiquitination pathway and controls MYC protein stability and activity. In this mini-review, we will summarize current updates regarding MYC ubiquitination and provide perspectives about these MYC regulators as potential therapeutic targets in cancer.